Elucidation of clinical and laboratory features, comorbidity risks, treatment options and molecular pathophysiology of antiphospholipid syndrome (APS) patients - Islam, Md Asiful (2018)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterised by the presence of circulating antiphospholipid antibodies (aPLs) such as lupus anticoagulant (LA), anticardiolipin (aCL) and anti-β2-glycoprotein I (β2-GPI) antibodies to phospholipid binding proteins. Although the disease has been in existence for approximately 35 years, the diagnostic criteria, risk factors, pathogenesis, genetic aspects, treatment strategies are poorly understood and have yet to be fully developed. In this study, the clinical and laboratory features, genetic risk factors, comorbidity risks, molecular pathophysiology and optimal treatment strategy of APS patients are explored. Human peripheral blood mononuclear cell (PBMC)-derived high-quality and integrity RNA extraction and purification method was optimised (centrifugal speed: 14000 rpm + spin time: 75 seconds + DNase treatment + Ribolock RNase inhibitor + RNA clean-up) which could be used to send APS patients’ RNA for RNA-Seq. In quest of APS patients, two studies were conducted. Firstly, on a familial primary APS cases from Sarawak, Malaysia, patients however became seronegative following long warfarin therapy. Another one with APS subjects from Hospital Universiti Sains Malaysia (HUSM) were retrospectively investigated by exploring the clinical, laboratory and treatment strategies. High occurrence of pregnancy morbidity, as well as some unusual clinical features such as persistent dysfunction of liver and kidneys; menorrhagia and ovarian cyst were observed. The use of medium-intensity warfarin was successful in preventing thrombosis recurrence. Additionally, since theHUSM patients were unwilling to participate in this study, we were unable to send the RNA samples for RNA-Seq to BGI. A systematic review with bioinformatic analyses was conducted to identify the genetic risk factors in thrombotic APS subjects where 16 genes were significantly associated with thrombosis affecting mostly the blood coagulation pathway and the immune system related to APS. Overall, three systematic reviews and meta-analyses were conducted to determine the influence of aPLs in patients with migraine, epilepsy and dementia without autoimmune disease as compared to controls, where aPLs were significantly comorbid with the said manifestations. Therefore, the neurologic features were early clinical manifestations before the development of full-blown APS. A single Cochrane systematic review was developed to explore the optimum treatment strategy for thrombotic APS subjects, where, moderate-intensity warfarin was superior than high-intensity warfarin. Overall, a comprehensive study exploring the clinical and laboratory features, genetic risk factors, comorbidity risks, molecular pathophysiology and optimal treatment strategy of APS patients was successfully established. Antiphospholipid syndrome (APS) is a systemic autoimmune disease characterised by the presence of circulating antiphospholipid antibodies (aPLs) such as lupus anticoagulant (LA), anticardiolipin (aCL) and anti-β2-glycoprotein I (β2-GPI) antibodies to phospholipid binding proteins. Although the disease has been in existence for approximately 35 years, the diagnostic criteria, risk factors, pathogenesis, genetic aspects, treatment strategies are poorly understood and have yet to be fully developed. In this study, the clinical and laboratory features, genetic risk factors, comorbidity risks, molecular pathophysiology and optimal treatment strategy of APS patients are explored. Human peripheral blood mononuclear cell (PBMC)-derived high-quality and integrity RNA extraction and purification method was optimised (centrifugal speed: 14000 rpm + spin time: 75 seconds + DNase treatment + Ribolock RNase inhibitor + RNA clean-up) which could be used to send APS patients’ RNA for RNA-Seq. In quest of APS patients, two studies were conducted. Firstly, on a familial primary APS cases from Sarawak, Malaysia, patients however became seronegative following long warfarin therapy. Another one with APS subjects from Hospital Universiti Sains Malaysia (HUSM) were retrospectively investigated by exploring the clinical, laboratory and treatment strategies. High occurrence of pregnancy morbidity, as well as some unusual clinical features such as persistent dysfunction of liver and kidneys; menorrhagia and ovarian cyst were observed. The use of medium-intensity warfarin was successful in preventing thrombosis recurrence. Additionally, since theHUSM patients were unwilling to participate in this study, we were unable to send the RNA samples for RNA-Seq to BGI. A systematic review with bioinformatic analyses was conducted to identify the genetic risk factors in thrombotic APS subjects where 16 genes were significantly associated with thrombosis affecting mostly the blood coagulation pathway and the immune system related to APS. Overall, three systematic reviews and meta-analyses were conducted to determine the influence of aPLs in patients with migraine, epilepsy and dementia without autoimmune disease as compared to controls, where aPLs were significantly comorbid with the said manifestations. Therefore, the neurologic features were early clinical manifestations before the development of full-blown APS. A single Cochrane systematic review was developed to explore the optimum treatment strategy for thrombotic APS subjects, where, moderate-intensity warfarin was superior than high-intensity warfarin. Overall, a comprehensive study exploring the clinical and laboratory features, genetic risk factors, comorbidity risks, molecular pathophysiology and optimal treatment strategy of APS patients was successfully established.